Pandemic Government: Pemerintah dan Masyarakat dalam Menanggulangi Covid-19 - Rema Marina; Tri Nugroho (Jurnal Pemerintahan dan Politik, 2023)
The Corona Virus Disease 2019 (Covid-19) pandemic has plagued the Indonesian nation since March 20, 2020. Some scientists, through their studies, tend to say that governments fail and society goes by its own behavior. Is that right? On that reality, researchers are interested in conducting studies with the aim of answering the problem of how pandemic government is formed? and critiquing it from the perspective of Government Ethics. The research method used is the critical-ethical method, which falls within the scope of the critical-transcendental method of Neo-Scholasticism. Data collection techniques using observation literature plot, in-depth interaction with selected literature and documentation. Data Analysist used hermeneutic-etis methods. The results of this study indicate that in the face of the threat of Covid-19 and an abnormal situation, it turns out that the pandemic government is able to form itself and the government continues to exist with teleological and contextual methods. This means that the pandemic government is formed through the art of governing: governing, managing, serving. On the one hand, the government remains attentive to the existing laws, communications, administration, management, as far as it can help in achieving the goal and on the other hand does not want to be entangled by all the rules, using the political power it has.